2019
DOI: 10.1111/1468-4446.12658
|View full text |Cite
|
Sign up to set email alerts
|

Parental values in the UK

Abstract: This article investigates the extent to which parental values differ between social groups in the UK at the start of the twenty‐first century. The study of parental values is an important area of sociological enquiry that can inform scholarship from across the social sciences concerned with educational inequality and cultural variability in family life. We draw on data from the Millennium Cohort Study to show how parent’s social class, religion, religiosity, race and ethnicity, and education are related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
(69 reference statements)
1
16
0
Order By: Relevance
“…Our results strongly support Kohn’s main thesis that occupational differences, and opportunities for self‐direction on the job, exert a salutary influence on values for self‐direction versus conformity . Although our results endorse Kohn’s main thesis, we have arrived at this conclusion through a different—and some would argue superior (see Baker and Barg 2019)—approach. Using a set of micro‐classes defined by Weeden and Grusky’s occupational categories, we employed effect proportional scaling to maximize the relationship of the occupational categories to child‐rearing values.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Our results strongly support Kohn’s main thesis that occupational differences, and opportunities for self‐direction on the job, exert a salutary influence on values for self‐direction versus conformity . Although our results endorse Kohn’s main thesis, we have arrived at this conclusion through a different—and some would argue superior (see Baker and Barg 2019)—approach. Using a set of micro‐classes defined by Weeden and Grusky’s occupational categories, we employed effect proportional scaling to maximize the relationship of the occupational categories to child‐rearing values.…”
Section: Discussionsupporting
confidence: 54%
“…Still, it can be shown that some of the educational differences (roughly one‐fourth) are mediated by occupation, so it can clearly be said that occupational class is an important factor in the understanding of child‐rearing values. These findings regarding the relative impacts of education and occupation are reinforced by recent cross‐national findings for the UK (Barker and Barg 2019). Within this framework we also examined whether there exists a strengthening of the relationship between religion and child‐rearing values over time, explicitly testing the hypothesis advanced by Starks and Robinson (2005) that the relationships between religious conservatism and child‐rearing orientations are growing stronger over time.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…These findings also contribute to work that uses the sociology of culture to understand gun culture (Carlson 2015; Mencken and Froese 2019) and build on the reemergent values literature in sociology (Baker and Barg 2019; Hitlin and Vaisey 2013; Longest, Hitlin, and Vaisey 2013; Miles 2015; Prasad et al 2009; Silver and Silver 2019; Vaisey and Miles 2014; Wuthnow, 2018) by bridging political sociology (Lipset 1963a, 1963b, 1989), the sociology of culture (Miles 2015; Vaisey and Miles 2014), and moral psychology (Haidt 2012). This article then constitutes a link between qualitative and cognitive approaches to values (Wuthnow 2008, 2018).…”
Section: Resultsmentioning
confidence: 57%